The establishment, optimisation, and transplantation of a three-dimensional bioprinted syngeneic granuloma model into C57BL/6 mice. - Mahabeer, Yastika (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.